Kinerja Produksi Ikan Lele (Clarias gariepinus sp) dengan Ukuran Tebar Berbeda Pada Sistem Akuaponik - Eko Harianto; Tatag Budiardi (Universitas Batangahari Jambi, 2021)
Catfish (Clarias gariepinus Burchell, 1822) is a type of freshwater fish that is prospectively cultivated. This study aims to analyze the production performance and economic analysis of catfish on aquaponics technology with floating raft systems. This research was conducted descriptively with two treatments and four replications. The treatments included fish sizes, which were 6-9 cm (A) and 3-4 cm (B). The fish used were fish with an initial weight of 7.13±1.30 g and 4.11±0.43 g, the plant used was water spinach (Ipomoea reptans poir) with an initial height of 8-10 cm. The results showed that there was a trend of increasing fish weight during the study from 7.13±1.30 g and 4.11±0.43 g to 110.02±6.09 g and 86.44±5.00 g at the end of the study. . The survival rate value during the study was 100% for all treatments, the feed conversion value ranged from 1.48-1.59. The highest specific weight growth rate was 1.60%/day. Water spinach production during catfish rearing can be done for 3 harvests. The analysis of the aquaponics business of the floating raft system is very efficient and profitable. The value of R/C ratio > 1 in all treatments means that the cultivation business is said to be feasible. Payback period of 0.57 years (A) and 0.19 years (B), the fastest return on investment is in treatment B. Aquaponics floating raft system with catfish stocking size 3-4 cm for 60 days of maintenance period provides the best production performance with SR value was 60.78%, specific weight growth rate was 0.051%/day, feed conversion was 1.18 and the best kale production was 75 kg. Economically, this research is feasible to do.